2019
DOI: 10.31910/rudca.v22.n2.2019.1344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación del rendimiento y calidad del fruto de parentales e híbridos de lulo de Castilla

Abstract: 0000-0001-9222-4674 3 municipios de La Florida y Buesaco, ubicados en el departamento de Nariño, se establecieron dos ensayos, bajo un diseño de Bloques Completos al Azar, con tres repeticiones. La interacción genotipo por ambiente fue signifi cativa para el peso de fruto (PF), diámetro ecuatorial, sólidos solubles totales, contenido de jugo y rendimiento (RTO). En La Florida, B1, B2, B3, B4xB5 y B2XLaSelva fueron los de mejor comportamiento en cuanto a RTO, con promedios entre 6,64 a 9,35t.ha -1 y PF, con 143… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
1
1
Order By: Relevance
“…These authors analyzed an initial population of 50 half-sibling lulo families to select those with improved fruit quality. The average weights in this study were also greater than the average weight of 97.29 g reported by Lagos-Santander et al (2019), who assessed selected parents and hybrids based on performance characteristics. These authors, however, found weights up to 167 g in one hybrid and 148 g in a parent, demonstrating that FW interacts with the environment and its performance is associated with SCA effects that result from parental dominance, as reported here.…”
Section: Specific Combining Ability (Gca)contrasting
confidence: 68%
See 2 more Smart Citations
“…These authors analyzed an initial population of 50 half-sibling lulo families to select those with improved fruit quality. The average weights in this study were also greater than the average weight of 97.29 g reported by Lagos-Santander et al (2019), who assessed selected parents and hybrids based on performance characteristics. These authors, however, found weights up to 167 g in one hybrid and 148 g in a parent, demonstrating that FW interacts with the environment and its performance is associated with SCA effects that result from parental dominance, as reported here.…”
Section: Specific Combining Ability (Gca)contrasting
confidence: 68%
“…For the PA, no positive and significant GCA effects were found; however, parental 3 had a negative effect (-1.31*), indicating the below-average performance of its hybrid combinations. Lagos-Santander et al (2019) and Lagos-Santander et al (2020) reported positive and significant correlations of PA with FW and Y, meaning this variable was associated with traits related to the production potential of lulo.…”
Section: General Combining Ability (Gca)mentioning
confidence: 92%
See 1 more Smart Citation
“…The strong relationship that occurs between yield and fruit number and diameter is due to the fact that these variables are components of this factor [23]. This argument is confirmed by [21] who stated that the number of fruits per plant is a parameter that is closely related to total production; that is, a greater number of fruits per plant with the same production per unit area shows that the fruits are smaller, therefore, this parameter allows determining the destination of the production, that is, for fresh market, large fruits are preferred (category 1 and 2) and small fruits (categories 3 and 4) are used for industry [24].…”
Section: Discussionmentioning
confidence: 99%
“…The lulo plant can be adapted to humid mountain forests and can grow in in areas with coffee cultivation (Coffea arabica L.), as was the case for the cloud forest of Huatusco, Veracruz [48,49].…”
Section: Soil Analysismentioning
confidence: 99%